52.8k views
2 votes
{b(1)=-2 {b(n)=b(n-1)-7 What’s the 3rd term?

User Wazz
by
6.0k points

2 Answers

6 votes

Answer: the answer is b(5)

Explanation:

To find the third term work backwards and plug it in. That was when you plug the solution of b(n-1) everything fits.

User MartinWebb
by
5.4k points
6 votes

Answer:

b(3)=-16

Explanation:

We have to figure out the second term

b(2)=b(1)-7

b(2)=-2-7

b(2)=-9

and now the third one

b(3)=b(2)-7

b(3)=-9-7

b(3)=-16

User Nicolas Schubhan
by
5.9k points